The Effect of Matching NIK as NPWP on Taxpayer Compliance: Income Tax OP Article 21 Employees at the Employment Social Security Organizing Agency in Greater Bandung - Bagus Darmawan Putra; Ibna Kamilia Fiel Afroh; Achmad Syahfrudin Zulkarnnaeni (West Science Accounting and Finance, 2024)
This study aims to determine the effect of NIK matching as NPWP on Taxpayer Compliance (PPh OP Article 21 Employees at the Employment Social Security Organizing Agency in Besuki Raya)". This study uses a quantitative method sourced from questionnaires. The population of this study is 90 employees. Sampling uses the census sampling method (saturated sampling), which is a sampling technique when all members of the population are used as samples. So the number of samples in this study is 90 respondents. The data analysis technique used is the SPSS computer program. The results of this study show that the matching of NIK as NPWP has a positive and significant effect on Taxpayer Compliance (Income Tax OP Article 21 Employees at the Employment Social Security Organizing Agency in Besuki Raya). Based on the results of the t-test, it can be seen that the variable of matching NIK as NPWP was obtained t calculated >t table (5,806>1,987) sig. 0.001 <0.07. The result of the determination coefficient (R2) in this study is 0.031 or 3.1%, which means that taxpayer compliance is influenced by the matching of NIK as NPWP by 3.1%. The result of the multiple linear regression test in the variable of matching NIK as NPWP is 0.551, if the coefficient has a positive value, it means that it has a positive effect on Taxpayer Compliance (Income Tax OP Article 21 Employees at the Employment Social Security Organizing Agency in Besuki Raya)".